A Study on Accounting Conservatism of Korean Lodging Companies. Issue 5 (2nd September 2020) - Shin, Wooyoung; Hong, Soonwook
ABSTRACT: This study aims to verify the accounting conservatism of lodging companies. As a result of analyzing the conservatism of lodging companies using models from Basu in 1997, Givoly and Hayn in 2000, and Penman and Zhang in 2002, it is shown that lodging companies are more conservative than manufacturing companies. Accounting is an indispensable element of management for any industry. There have been few studies on the accounting of Korean lodging companies. This paper is the first study to analyze the accounting behavior of lodging companies. In addition to academic contributions, in practice, lodging companies should pay more attention to accounting, and moreover, they should actively hire accounting professionals to achieve qualitative growth.